Sustainable Weed Management Using Chromolaena odorata Organic Mulch Improves Soybean Productivity - Kartono; Anuar Ramut; Muhammad Husaini Assauwab; Deden Sumoharjo; Muhammad Yassir; Mario Pani; Era Maulia; Yulis Untari (Warmadewa University Press, 2025)
Weed management is commonly achieved through herbicide application; however, excessive herbicide use may lead to weed resistance and environmental degradation. This study aimed to determine the effective dose of organic siam weed (Chromolaena odorata L King and Robinson) mulch for suppressing weeds and improving soybean growth and yield. The experiment was conducted in Lawe Sagu Hulu Village, Lawe Bulan Subdistrict, Aceh Tenggara Regency, Aceh Province, from August to December 2024. A non-factorial randomized complete block design was used with five mulch doses: 0, 4.8, 9.6, 14.4, and 19.2 t ha-1, each replicated four times. Experimental plots 2.5 × 2.5 m were prepared through standard tillage, and chopped siam weed mulch 10 cm was applied to the soil surface at planting according to treatments. Observed variables included root and plant fresh weight, weed control percentage, weed species number, weed fresh weight, seed weight, and 100-seed weight. Data were analyzed using SPSS version 16, and significant effects were further tested with Duncan’s New Multiple Range Test. Application of 4.8 t ha-1 mulch improved weed control percentage, while higher doses of 14.4–19.2 t ha-1 effectively reduced weed species number and weed fresh weight at 30 days after treatment, as well as increased root fresh weight at 40 days and soybean fresh weight at 20 and 40 days after treatment.